2011
DOI: 10.1021/jf202167b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Hazelnut (Corylus avellana) in Cookies: ELISA versus Real-Time PCR

Abstract: Hazelnuts (Corylus avellana) are used widely in the food industry, especially in confectionery, where they are used raw, roasted, or in a processed formulation (e.g., praline paste and hazelnut oil). Hazelnuts contain multiple allergenic proteins, which can induce an allergic reaction associated with symptoms ranging from mild irritation to life-threatening anaphylactic shock. To date, immunochemical (e.g., ELISA or dipstick) and PCR-based analyses are the only methods available that can be applied as routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…matrix effects) and by the effect of food processing (e.g. heat treatments, formation of Maillard products, fermentation, partial hydrolysis) Cucu et al, 2013;Garber and Perry, 2010;Pele et al, 2007;Platteau et al, 2011a;Platteau et al, 2012;Roder et al, 2009). To address the referred issues, some studies have been conducted aiming at evaluating the performance of commercial kits from different brands to detect hazelnut traces in processed foods Garber and Perry, 2010).…”
Section: Elisa Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…matrix effects) and by the effect of food processing (e.g. heat treatments, formation of Maillard products, fermentation, partial hydrolysis) Cucu et al, 2013;Garber and Perry, 2010;Pele et al, 2007;Platteau et al, 2011a;Platteau et al, 2012;Roder et al, 2009). To address the referred issues, some studies have been conducted aiming at evaluating the performance of commercial kits from different brands to detect hazelnut traces in processed foods Garber and Perry, 2010).…”
Section: Elisa Systemsmentioning
confidence: 99%
“…Using the classical SYBR Green I or the enhancement of SYBR GreenER, several real-time PCR systems have been described with high specificity and sensitivity to trace hazelnut allergens in foods (D'Andrea et al, 2009;D'Andrea et al, 2011;Iniesto et al, 2013;Pafundo et al, 2010). As alternative and for the unequivocal identification of hazelnut in complex food matrices, other studies have demonstrated the use of specific hydrolysis probes to enhance the specificity of the reaction (Arlorio et al, 2007;Costa at al., 2012b;Costa et al, submitted;Köppel et al, 2010;Köppel et al, 2012;Piknová et al, 2008;Platteau et al, 2011a;Platteau et al, 2011b), based on the complementarity of a third hybridisation oligonucleotide during the amplification.…”
Section: Pcr Systemsmentioning
confidence: 99%
“…Thanks to their flavour, hazelnuts are often used in food production, especially in confectionery: they are often found in pastries, chocolate spreads, ice creams, cereal bars, cookies, nougat, etc. (Platteau et al, 2011).…”
mentioning
confidence: 99%
“…Hazelnuts are usually processed integrally into food products, although hazelnut oil is also often used for cooking (Platteau et al 2011). Due to the positive changes of its organoleptic properties during the roasting process, hazelnut is generally roasted before using it in sweets, confectionery, chocolate and biscuits (Demir & Cronin 2005).…”
mentioning
confidence: 99%
“…For the detection and quantification of hazelnut in foods, several techniques have been developed, either directly targeting the allergen or other marker proteins (Ansari, Stoppacher, & Baumgartner, 2012;Cucu et al, 2010;Garber & Perry, 2010;Platteau, De Loose, De Meulenaer, & Taverniers, 2011a;Trashin, Cucu, Devreese, Adriaens, & De Meulenaer, 2011) or indirectly via DNA analysis (Arlorio, Cereti, Coisson, Travaglia, & Martelli, 2007;Costa, Mafra, Kuchta, & Oliveira, 2012b;D'Andrea et al, 2011;Platteau, De Loose, De Meulenaer, & Taverniers, 2011b;Platteau et al, 2011a). In the field of protein-based methods, the enzymelinked immunosorbent assays (ELISA) are among the most used approaches for allergen detection (Schubert-Ullrich et al, 2009).…”
Section: Introductionmentioning
confidence: 99%